2021
DOI: 10.1109/access.2021.3117261
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial Dyeing Recipe Recommendation System for Textile Fabrics Based on Data-Mining and Modular Architecture Design

Abstract: for very helpful discussion regarding the design of the system framework, Ms. Yaguang Wang for performing data cleaning for the industrial dataset used in this work, Mr. Zhiwen Tu for regression model training, and Miss Yawen Yin for the proof-reading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The multivariate linear regression modeling is conducted on an industrial dyeing dataset which has been reported in the earlier report [14]. The dataset is consisted of 810 industrial dyeing records for rayon fabrics using a combination of three reactive dyes (CRD-red, CRD-Navy blue and CRD-yellow).…”
Section: Data Collection and The Settings For Regression Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…The multivariate linear regression modeling is conducted on an industrial dyeing dataset which has been reported in the earlier report [14]. The dataset is consisted of 810 industrial dyeing records for rayon fabrics using a combination of three reactive dyes (CRD-red, CRD-Navy blue and CRD-yellow).…”
Section: Data Collection and The Settings For Regression Modelingmentioning
confidence: 99%
“…where ݇ is the i-th model parameter (݇ stands for the constant term); R, G and B stand for the RGB values; L, a and b stand for the CIELAB values. The complete dataset is randomly divided into two parts for model training and testing under a ratio of 60% to 40%, which is under the same setting as in reference [14]. Mean absolute error (MAE), mean absolute percent error (MAPE) and weighted absolute percent error (WAPE) are used to quantify the model performance.…”
Section: Data Collection and The Settings For Regression Modelingmentioning
confidence: 99%
See 3 more Smart Citations